Diaspora in two Caribbean Novels: Levy´s Small Island and Phillips´s A State of Independence - Bonnici, Thomas (Revista de Letras, 2007)
The novels Small Place by Andrea Levy and A State of Independence by Caryl Phillips, respectively published in 2004 and in 1986, are analyzed. Since both deal with the trasnational diaspora of Caribbeans migrating to Britain, postcolonial problems concerning home and identity in the colonial subjects are discussed and the processes involving the diasporic agente are problematized. Results show that the subjectivity of the colonial transmigrant is constructed either by interventions within racialized society or by disruptions against colony-minded native rulers sticking to the status quo. Diáspora em dois romances caribenhos: Small Island, de Levy e A State of Independence, de Philips Analisam-se os romances Small Place, de Andréa Levy, e A State of Independence, de Caryl Phillips, publicados em 2004 e 1986 respectivamente. Como a diáspora transnacional de caribenhos migrando à Inglaterra é o tema dos dois romances, discutem-se os problemas pós-coloniais dos conceitos envolvendo o lar e a identidade nos sujeitos coloniais e problematiza-se a formação do agente diaspórico. Os resultados mostram que a subjetividade do transmigrante colonial é construída ou através de intervenções na sociedade racista ou através da subversão contra os dirigentes nativos que querem preservar egoisticamente a situação colonial.